Pemberdayaan Sumber Daya Alam Untuk Kebutuhan Ekonomi Masyarakat Dalam Pandemi Covid-19 - Jimmi Pindan Pute (Institut Agama Kristen Negeri Toraja, 2021)
The outbreak of a pandemic has hampered various aspects of human life. One of them is the decline in economic needs, which is caused by work stops at the suggestion of the government to stay at home. The research relates to the life of the community in the village of the Sa'dan sub-district, especially on economic problems due to the COVID-19 outbreak by encouraging the community to empower the natural environment. Some activities that can be carried out by the community are: nature management, provision of vegetable seeds and fertilizers. Methods This research uses descriptive and ethnographic approaches. Data collection is related to the life of the community in the village of Sa'dan sub-district, especially on economic problems due to the covid 19 outbreak. This research was conducted to provide assistance to the community in learning to love nature as a gift from God. The results of research by the government and the church will work together in empowering the community through fostering and distributing vegetable seeds and some pets which will be given to community members and the results can be enjoyed and traded back to the government or other places. Maraknya wabah pandemi menghambat berbagai sendi kehidupan manusia. Salah satu diantaranya adalah menurunnya kebutuhan ekonomi, yang disebabkan oleh karena pekerjaan yang berhenti atas anjuran pemerintah untuk tetap tinggal di rumah. Penelitian tersebut berkaitan dengan kehidupan masyarakat di desa kecamatan Sa’dan terkhusus pada masalah prekonomian akibat wabah covid 19 dengan tindakan mendorong masyarakat untuk memberdayakan alam sekitar. Beberapa kegiatan yang dapat dilakukan oleh masyarakat yaitu: pengelolaan alam, penyediaan bibit sayuran dan pupuk. Metode Penelitian ini menggunakan pendekatan deskriptif dan etnografi. Pengumpulan data berkaitan dengan kehidupan masyarakat di desa kecamatan Sa’dan terkhusus pada masalah ekonomi akibat wabah covid 19 dengan menggunakan metode analisis dan wawancara. Penelitan ini dilakukan untuk memberikan pendampingan kepada masyarakat dalam belajar mencintai alam sebagai karunia dari Allah. Hasil penelitian pemerintah dan gereja akan bekerja sama dalam memberdayakan masyarakat melalui pembinaan dan pembagian bibit sayuran dan beberapa hewan peliharaan yang akan diberihkan kepada warga masyarakat dan hasilnya dapat dinikmati dan diperjual belihkan kembali kepada pemerintah ataupun ketempat lainnya.